Immunohistochemical Characterization of Canine Prostatic Intraepithelial Neoplasia - Matsuzaki, P.; Cogliati, B.; Sanches, D. S.; Chaible, L. M.; Kimura, K. C.; Silva, T. C.; Real-Lima, M. A.; Hernandez-Blazquez, F. J.; Laufer-Amorim, R. [UNESP]; Dagli, M. L. Z. (Elsevier B.V., 2010)
The development of prostate cancer is believed to be a multistep process, progressing sequentially from normal epithelium, to prostatic intraepithelial neoplasia (PIN) and, finally, to invasive neoplasia. Malignant stem cells within the basal cell layer of the prostatic epithelium are believed to play an important role in the failure of androgen-ablation therapy that occurs in the most advanced form of prostate cancer. The aim of the present study was to immunohistochemically characterize the lesions of canine PIN. Prostatic tissue from five dogs with PIN was compared with normal prostate tissue from nine further dogs. There was an increase in the number of basal epithelial cells in lesions consistent with PIN as defined by expression of the nuclear protein p63. These lesions had elevated expression of proliferating cell nuclear antigen (PCNA) and heterogeneous labelling for the nuclear androgen receptor (AR). These findings suggest that the basal cells present in PIN may play a role in canine prostate carcinogenesis and that the proliferation of these cells occurs despite the heterogeneous expression of the AR. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: androgen receptor; basal cell; dog; prostatic intraepithelial neoplasia